A JURIDICAL ANALYSIS OF THE ROLE OF HOSPITAL MANAGEMENT IN OPTIMIZING HEALTHCARE SERVICES: A CASE STUDY AT REGINA MARIS HOSPITAL - Revelino Pangaribuan; Tamaulina Br. Sembiring (International Journal of Synergy in Law, Criminal, and Justice, 2025)
This study discusses the initial limits of authority of hospital management in improving the quality of health services, with a case study at Regina Maris Hospital, Medan. Hospitals as public service institutions have complex structures that require professional management within a legal framework. The focus of the study includes: (1) the initial limits of authority of hospital management in managing service quality, (2) legal and administrative factors that influence this authority, and (3) challenges and solutions in its implementation. The method used is normative juridical with an analysis of statutory regulations, legal doctrine, as well as Gustav Radbruch's theory of legal certainty and AV Dicey's theory of administrative law. The research results show that Regina Maris Hospital management has exercised its authority in accordance with the principles of legality and accountability, including in establishing service standards, managing human resources, implementing a hospital management information system (SIMRS), and guaranteeing patient rights. Regulatory factors such as accreditation obligations and competency standards serve as the main limits of authority. Challenges faced include limited human resources, delays in adopting information technology, and financial management constraints. Nevertheless, Regina Maris Hospital has implemented solutions in the form of ongoing training, educational collaboration, internal audits, and service financing innovations. This study recommends that hospital management adapt its managerial systems to regulatory and technological developments, strengthen human resources, and encourage digital transformation in healthcare services. A regulatory-based and accountable approach will establish hospitals as institutions that ensure quality service, fairness, and legal protection for the community on a sustainable basis.